(untitled) (Bangladesh Journal of Medical Science, 2011)
Oligodontia (severe partial anodontia) is a rare developmental dental anomaly refers to congenital lack of more than six teeth. Most often oligodontia appears as part of some congenital syndromes that affects several organ systems. The exact etiology for oligodontia is unknown. Management includes various restorative and orthodontic procedures to improve the esthetics and function. The present article reports a case of oligodontia of 14 number of permanent teeth excluding third molars in a non-syndromic female patient. Key words: oligodontia; hypodontia, partial anodontia, tooth agenesis. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8365 BJMS 2011; 10(3): 200-202